Regulating Anger under Stress via Cognitive Reappraisal and Sadness - Zhan, Jun; Wu, Xiaofei; Fan, Jin; Guo, Jianyou; Zhou, Jianshe; Ren, Jun; Liu, Chang; Luo, Jing (Frontiers in Psychology, 2017)
Previous studies have reported the failure of cognitive emotion (CR) regulation, especially in regulating unpleasant emotions under stress. The underlying reason for this failure was the application of CR depends heavily on the executive function of the prefrontal cortex (PFC), but this function can be impaired by stress-related neuroendocrine hormones. This observation highlights the necessity of developing self-regulatory strategies that require less top-down cognitive control. Based on traditional Chinese philosophy and medicine, which examine how different types of emotions promote or counteract one another, we have developed a novel emotion regulation strategy whereby one emotion is used to alter another. For example, our previous experiment showed that sadness induction (after watching a sad film) could reduce aggressive behavior associated with anger (i.e., “sadness counteracts anger”) (Zhan, Ren, Fan, & Luo. 2015. Distinctive effects of fear and sadness induction on anger and aggressive behavior. Front. Psychol. 6, 725). Relative to the CR strategy requiring someone to think about certain cognitive reappraisals to reinterpret the meaning of an unpleasant situation, watching a film or listening to music and experiencing the emotion contained therein seemingly requires less cognitive effort and control; therefore, this “sadness counteracts anger” (SCA) strategy may be an alternative strategy that compensates for the limitations of cognitive regulation strategies, especially in stressful situations. The present study was designed to directly compare the effects of the CR and SCA strategy in regulating anger and anger-related aggression in stressful and non-stressful conditions. Participants' subjective feeling of anger, anger-related aggressive behavior, skin conductance, and salivary cortisol and alpha-amylase (sAA) levels were measured. Our findings revealed that acute stress impaired one’s ability to use CR to control angry responses provoked by others, whereas stress did not influence the efficiency of the SCA strategy. Compared with sadness or neutral emotion induction, CR induction was found to reduce the level of subjective anger more, but this difference only existed in non-stressful conditions. By contrast, irrespective of stress, the levels of aggressive behavior and related skin conductance after sadness induction were both significantly lower than those after CR induction or neutral emotion induction, thus suggesting the immunity